2017
DOI: 10.1007/s12282-017-0820-x
|View full text |Cite
|
Sign up to set email alerts
|

UBAP2L silencing inhibits cell proliferation and G2/M phase transition in breast cancer

Abstract: BackgroundUbiquitin-associated protein 2-like (UBAP2L) contains a ubiquitin-associated domain near its N-terminus, which has been demonstrated to be overexpressed in multiple tumors, including hepatocellular carcinoma and colorectal carcinoma but its role has not been well studied in breast cancer. Thus, this study was designed to evaluate whether UBAP2L can serve as a potential molecular target for breast cancer therapy.MethodsThe expression of UBAP2L was determined in breast cancer tissues and cell lines by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 25 publications
3
34
0
Order By: Relevance
“…It can interact with BIM1 to form a complex that modulates hematopoietic stem cell activity [24]. Numerous studies indicated its association with various types of cancer [25][26][27][28][29][30]. It is required for the accurate distribution of chromosomes during mitosis [31].…”
Section: Introductionmentioning
confidence: 99%
“…It can interact with BIM1 to form a complex that modulates hematopoietic stem cell activity [24]. Numerous studies indicated its association with various types of cancer [25][26][27][28][29][30]. It is required for the accurate distribution of chromosomes during mitosis [31].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from neurodegeneration, a number of publications show a role of UBAP2L in cancer. UBAP2L appears to act in different malignances as an oncogene, whose expression is required for survival (Chai et al, 2016), growth (He et al, 2018; Li and Huang, 2014; Li et al, 2018; Zhao et al, 2015), and metastasization (Aucagne et al, 2017; Li and Huang, 2014; Li et al, 2018; Ye et al, 2017). Stress granules are often present in cancer cells (reviewed in Mahboubi and Stochaj, 2017), where they may promote cell survival in the stressful condition of the cancer microenvironment (Adjibade et al, 2015; Somasekharan et al, 2015; Vilas-Boas et al, 2016) and metastasization (Somasekharan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The relative stability of stress granule cores has recently allowed their purification and the identification of novel stress granule nucleators, among them the protein UBAP2L (Ubiquitin-associated protein 2-like (Markmiller et al, 2018; Youn et al, 2018). UBAP2L is a ubiquitous and abundant protein in human tissues (Beck et al, 2011; Lonsdale et al, 2013; Melé et al, 2015; Uhlén et al, 2015), it promotes cancer progression and metastasis (Aucagne et al, 2017; Chai et al, 2016; He et al, 2018; Li and Huang, 2014; Li et al, 2018; Ye et al, 2017, P. 20; Zhao et al, 2015) and may be involved in neurodegenerative diseases (Markmiller et al, 2018). Despite its abundance and potential implication in diseases, the exact role of UBAP2L in cell physiology and stress granule formation is not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…After the functional enrichment analysis, we found that some enriched biological processes were reported to be associated with tumor progression. For example, i) cell adhesion was usually reported to show a reduced number of tumor cells since 1962 (Holmberg 1962); ii) autophagic cell death occurs via the activation of autophagy, which has been reported to play roles in tumor suppression (Mathew et al 2009); iii) the positive regulation of cell proliferation is a common characteristic of cancer, and the inhibition of cancer cell proliferation may serve as a potential target for cancer treatment (He et al 2018); iv) changes in extracellular matrix organization were reported with crucial roles in cancer metastasis (Goreczny et al 2017;Sada et al 2016); v) positive regulation of blood coagulation was frequently reported in cancer progression (Tikhomirova et al 2016); and vi) angiogenesis is still considered a common characteristic of tumorigenesis in many studies (Baltrunaite et al 2017;Protopsaltis et al 2019;Ziegler et al 2016).…”
Section: Discussionmentioning
confidence: 99%